2018
DOI: 10.4110/in.2018.18.e8
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Osteoclast Differentiation by Cytokine Networks

Abstract: Cytokines play a pivotal role in maintaining bone homeostasis. Osteoclasts (OCs), the sole bone resorbing cells, are regulated by numerous cytokines. Macrophage colony-stimulating factor and receptor activator of NF-κB ligand play a central role in OC differentiation, which is also termed osteoclastogenesis. Osteoclastogenic cytokines, including tumor necrosis factor-α, IL-1, IL-6, IL-7, IL-8, IL-11, IL-15, IL-17, IL-23, and IL-34, promote OC differentiation, whereas anti-osteoclastogenic cytokines, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
333
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(363 citation statements)
references
References 127 publications
4
333
0
8
Order By: Relevance
“…A close relation between bone turnover and the immune system has been previously shown by Ginaldi et al (14). Various proinflammatory cytokines, such as TNF-a and IL-1b, have been associated with increased bone turnover by affecting osteoclast differentiation and function (4,(15)(16)(17).…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…A close relation between bone turnover and the immune system has been previously shown by Ginaldi et al (14). Various proinflammatory cytokines, such as TNF-a and IL-1b, have been associated with increased bone turnover by affecting osteoclast differentiation and function (4,(15)(16)(17).…”
mentioning
confidence: 69%
“…Both osteoclast differentiation and activation of the resorptive activity are tightly regulated, and therefore, deregulation of these processes, due to hyperinflammation, for example, leads to serious dysfunctioning of the bone tissue (4,5).…”
mentioning
confidence: 99%
“…These signals might regulate ALD hHSC/mHSC activation, motility, and the cross talk between alcohol‐damaged hepatocytes and Kupffer cells/macrophages. Remarkably, a combination of five to six of these genes was associated with astroglial sensome in Alzheimer's disease, amyotrophic lateral sclerosis, and osteoclasts differentiation, outlining the functional commonalities of these genes for disease manifestation in various tissues.…”
Section: Discussionmentioning
confidence: 96%
“…[38][39][40] IL-6 is a potential inducer of the osteoclast differentiation independent of RANKL and IL-6 receptor inhibition results in the blockage of the osteoclast formation both in vitro and in vivo. [41][42][43] Thus, inhibition of inflammation represents a promising therapeutic approach to treated wear debris-induced inflammatory osteolysis. 44 In the present study, our results suggested that the inhibition of pro-inflammatory cytokines by an H 2 S donor markedly decreased the presence of osteoclasts in murine models.…”
Section: Discussionmentioning
confidence: 99%